Standardization of Seagrass Biophysical Parameterization for Wave Attenuation in Nature-Based Coastal Protection: A Systematic Review Based on PRISMA - Fathimah Az-Zahro Mahmud; Nizam; Benazir (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
Nature-based coastal protection is increasingly being developed as an alternative to conventional infrastructure, with seagrass meadows playing a crucial role in wave attenuation and sediment stabilization. However, the characterization of seagrass biophysical parameters used in hydrodynamic modeling remains unstandardized. This study aims to synthesize seagrass biophysical characterization methods and their application in wave attenuation modeling to support nature-based coastal protection. The study used a Systematic Literature Review guided by PRISMA. The study population included all relevant scientific publications, while the sample consisted of 30 articles that met the inclusion criteria. The research instrument was a structured data extraction protocol that included study characteristics, biophysical parameters, modeling approaches, and hydrodynamic indicators. These were then analyzed descriptively and comparatively through narrative synthesis. The results showed that stand density, canopy height, leaf dimension and stiffness, and biomass were the main parameters most consistently used to represent wave attenuation, although there were still variations in measurement methods and parameterizations between studies. In conclusion, harmonization of biophysical characterization protocols and the development of multiscale parameterizations are needed to improve modeling accuracy and the implementation of seagrass-based coastal protection solutions.